112k views
1 vote
Use f(x) = 1 2 x and f -1(x) = 2x to solve the problems. In general, f−1(f(x)) = f(f−1(x)) =

User Recluze
by
5.6k points

2 Answers

5 votes

Answer:

the answer is, x

Explanation:

edge 2020

User Fredericka
by
5.3k points
4 votes

ANSWER


{f}^( - 1)( f(x)) = f( {f}^( - 1) ( x)) = x

EXPLANATION

The given functions are;


f(x) = (1)/(2) x


{f}^( - 1) (x) = 2x


f( {f}^( - 1) (x)) = f(2x)


f( {f}^( - 1) (x)) = (1)/(2) * 2x = x

Also,


{f}^( - 1)( f(x)) = {f}^( - 1) ( (1)/(2) x)


{f}^( - 1)( f(x)) = 2 * (1)/(2) x = x

In general,


{f}^( - 1)( f(x)) = f( {f}^( - 1) ( x)) = x

User Noamtcohen
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.